Gender equality and economic independence: part-time work and self-employment. Review of the implementation of the beijing platform for aqtion in the EU Member States (Luxembourg, 2014)
"he report focuses on the importance of gender equality in economic rights and independence, including access to employment, appropriate working conditions and control over economic resources. Through an analytical focus on part-time work and self-employment, the report demonstrates their effect on the economic independence of women and men, as well as on gender equality more broadly. On the basis of this analysis, EIGE proposed a set of indicators and sub-indicators in the area of women and the economy that were endorsed by the Council in June 2014."